STRATEGI BADAN PENGAWAS PEMILU KABUPATEN SERANG DALAM PENCEGAHAN PRAKTIK POLITIK UANG - Muhammad Asmawi; Amiludin Amiludin; Edi Sofwan (Indonesian Journal of Law and Policy Studies, 2021)
The process of regional head election cannot be carried out with the wishes of the parties and at will, as a country that upholds the values of democracy and as a rule of law which is reformulated in article 1 paragraph 3 of the 1945 Constitution that the implementation of elections to the regions must be based on the value of justice. strategies in preventing illegal acts committed by election contestants to the regions, especially money politics against the community, the attacking regency election supervisory body needs to carry out socialization methods to the community and also political parties, as well as conduct anti-money politics patrols during the calm period which often occurs by the team. success. The research method that I use in writing this article is to use empirical normative legal research methods. The primary data source is the result of interviews with several members of the Bawaslu of Serang Regency. The data analysis in writing this article is a qualitative way. This is because in analyzing an object of research, this method is used to explain the data used.Keywords: Regional head elections, Election supervisory bodies, Strategy, Money Politics